2020
DOI: 10.2337/db19-0976
|View full text |Cite
|
Sign up to set email alerts
|

Elevated First-Trimester Neutrophil Count Is Closely Associated With the Development of Maternal Gestational Diabetes Mellitus and Adverse Pregnancy Outcomes

Abstract: Chronic low-grade inflammation plays a central role in the pathophysiology of gestational diabetes mellitus (GDM). To investigate the ability of different inflammatory blood cell parameters in predicting the development of GDM and pregnancy outcomes, 258 women with GDM and 1,154 women without were included in this retrospective study. First-trimester neutrophil count outperformed white blood cell count and the neutrophil-tolymphocyte ratio in the predictability for GDM. Subjects were grouped based on tertiles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 41 publications
2
41
0
Order By: Relevance
“…In addition, elevated neutrophil-derived products including nucleosomes, neutrophil elastase, and free DNA have been found in the plasma of diabetes mellitus patients [ 129 ]. Elevated first-trimester neutrophil count has also been associated with the development of GDM and adverse pregnancy outcomes [ 130 ]. In the placenta, extracellular traps formation may be triggered by infection (e.g., by bacteria or their products) or by inflammation (e.g., preeclampsia and GDM).…”
Section: Hyperglycemia-induced Metainflammation In Gdm Alters Placental Immune Cells Population Favoring An Inflammatory Cytokine Signatumentioning
confidence: 99%
“…In addition, elevated neutrophil-derived products including nucleosomes, neutrophil elastase, and free DNA have been found in the plasma of diabetes mellitus patients [ 129 ]. Elevated first-trimester neutrophil count has also been associated with the development of GDM and adverse pregnancy outcomes [ 130 ]. In the placenta, extracellular traps formation may be triggered by infection (e.g., by bacteria or their products) or by inflammation (e.g., preeclampsia and GDM).…”
Section: Hyperglycemia-induced Metainflammation In Gdm Alters Placental Immune Cells Population Favoring An Inflammatory Cytokine Signatumentioning
confidence: 99%
“…Many studies have reported that women with GDM had significantly higher counts of leukocytes, neutrophils, lymphocytes and monocytes ( 11 , 59 ). Furthermore, most clinical studies reported that the ratio of these cells is a suitable GDM marker - for example, an elevated neutrophil/lymphocyte ratio (NLR) and monocyte/lymphocyte ratio (MLR) ( 11 , 60 - 62 ).…”
Section: Whole Blood Parametersmentioning
confidence: 99%
“…The potent reason behind this activation of the inflammasome is excessive glucose which induces NLRP3 resulting in the generation of pro-inflammatory cytokine storms mainly IL-1β and IL-18 ( Figure 2C ) ( Han et al, 2015 ; Corrêa-Silva et al, 2018 ). Excessive neutrophilia, high glycaemic levels, and increased homeostatic model assessment of insulin resistance are associated with GDM diagnosis as early as in the first trimester ( Figure 2C ) ( Sun et al, 2020 ). The increased numbers of neutrophils are intended to be more reliable than leukocyte numbers i.e., the neutrophil to leukocyte ratio is used as an inflammatory marker for diagnosis of GDM in the second trimester.…”
Section: Introductionmentioning
confidence: 99%